Commodification and Trauma in Wordsworth’s Poetry: A Preface - Datta, Vija Kr.; Pandey, Beerendra (Journal of Advanced Academic Research, 2017)
Commodity refers to physical sexual desire to fulfill the material needs as well as to lead the luxurious life and the colonial system affects the life and literature society and everywhere. The Romantic period, particularly the time of Wordsworth, witnessed turbulent social upheaval due to the ascendancy of commodification in British life. Although the Romantic writers used to describe British life as reverberating with natural richness, it was actually a ploy to hide massive natural devastation as Jerome McGann’s alleges in The Romantic Ideology (1983). England, during the Romantic age, had been engulfed by modernization, deforestation, industrialization, urbanization and other different types of problems, including traumas.